Childrenâs Reading Difficulty and Their Perceived Misbehavior - Ocampo, Jr., Jose M (ASPENSI, 2015)
ABSTRACT: The greatest natural gift of a child as a growing and developing individual is the ability to learn. How good a child is in relation to reading and writing has been considered by many parents as a question they anticipate to encounter. The study sought to describe the 6-years-old childrenâs reading difficulty and their perceived misbehavior. It is worthy to note that misbehavior is a complaint not only limited to teachers or other school personnel. Sometimes, even parents or carers themselves agree that their children are exhibiting misbehaviors. For gathering of data, in this study, parents/carers and teachers of participants were interviewed focusing on the checklist. Results indicate that childrenâs learning difficulty in relation to reading is composed of attention, expressive reading, focusing on test, reading comprehension, and spelling. The behaviors occurring during reading sessions at home, among the respondents are grouped on four areas, such as: head, arm-hand, shoulder-waist, and waist-foot. Some carers, however, perceived these behaviors as misbehaviors. The study recommends that other areas of learning difficulty, especially concerning mathematics be explored. Aside from organizing modified group activities according to skills (for letter-sound recognition, proper blending, and reading comprehension with few words), explore and try-out some programs, which can be used as an alternative movement-based learning activity.KEY WORD: Children; Parents and Teachers; Reading Difficulty; Misbehaviour; Learning Activity.Â INTISARI: âKesulitan Anak-anak dalam Membaca dan Perilaku Nakal yang Dirasakan Merekaâ. Karunia alam terbesar bagi anak sebagai individu yang tumbuh dan berkembang adalah kemampuan untuk belajar. Seberapa baik anak dalam kaitannya dengan membaca dan menulis telah dianggap oleh kebanyakan orang tua sebagai pertanyaan besar untuk mengantisipasi dan menghadapinya. Penelitian ini berusaha untuk menggambarkan kesulitan membaca anak-anak berusia 6 tahun dan perilaku nakal yang dirasakan mereka. Hal ini layak untuk dicatat bahwa perilaku nakal adalah keluhan tidak hanya terbatas pada guru atau petugas sekolah lainnya. Kadang-kadang, bahkan orang tua atau wali murid sendiri setuju bahwa anak-anak mereka menunjukan perilaku nakal. Untuk mengumpulkan data, dalam penelitian ini, peserta orang tua/wali murid dan guru diwawancarai dengan fokus pada daftar nama-nama. Hasil penelitian menunjukan bahwa kesulitan belajar anak dalam kaitannya dengan membaca terdiri dari perhatian, membaca ekspresif, fokus pada tes, pemahaman bacaan, dan ejaan. Perilaku nakal yang terjadi selama sesi membaca di rumah, diantara para responden dikelompokkan pada empat bidang, seperti: kepala, lengan-tangan, bahu-pinggang, dan pinggang-kaki. Beberapa wali murid, bagaimanapun, menganggap perilaku ini sebagai kenakalan. Studi ini merekomendasikan bahwa area lain dari kesulitan belajar, terutama menyangkut matematika juga dieksplorasi. Selain menyelenggarakan kegiatan kelompok yang dimodifikasi sesuai dengan keterampilan (dengan surat pengakuan yang dibacakan, gabungan yang tepat, dan pemahaman bacaan dengan beberapa kata), mengeksplorasi dan menguji-cobakan beberapa program, yang dapat digunakan sebagai alternatif gerak berbasis aktivitas belajar.KATA KUNCI: Anak-anak; Orang Tua dan Guru; Kesulitan Membaca; Perilaku Nakal; Kegiatan Belajar.About the Author: Prof. Jose M. Ocampo, Jr., Ph.D. is a Lecturer at the PNU (Philippine Normal University) in Manila, the Philippines. For academic interests, the author is able to be contacted via e-mail at: juno_6970@yahoo.comHow to cite this article? Ocampo, Jr., Jose M. (2015). âChildrenâs Reading Difficulty and Their Perceived Misbehaviorâ in SIPATAHOENAN: South-East Asian Journal for Youth, Sports & Health Education, Vol.1(2) October, pp.199-208. Bandung, Indonesia: Minda Masagi Press, APAKSI Bandung, and KEMENPORA RI Jakarta, ISSN 2407-7348.Chronicle of the article: Accepted (May 16, 2015); Revised (July 27, 2015); and Published (October 28, 2015).